PEMERTAHANAN SUASANA KEJAWAAN DALAM NOVEL THE LAST CROWD KARYA OKKY MADASARI - Chrismalia Garnida, Susie; Sudarwati, Sudarwati (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
This article discusses how words from the Javanese language in Okky Madasari's novel Kerumunan Terakhir are preserved in the English translation of The Last Crowd by the same author. Translating from Javanese to English will certainly experience incompatibilities and strategies that can be used, but this does not happen because these words have their equivalents, and the novelist continues to use Javanese either directly, providing paraphrases, or include a translation in English. There are twelve data that use Javanese words, either at the word or sentence level. From the discussion of the overall data, it appears that the novelist tries to maintain the nuances of Javanese culture, especially Jogjakarta or more precisely, Puncak Suroloyo, Menoreh mountains, which of course is thick with the use of Javanese in their daily lives.